PENGARUH ORANG TUA DI ERA 4.0 TERHADAP PRESTASI BELAJAR SISWA DI MI ISLAMIYAH PINGGIRSARI TULUNGAGUNG - Wahyu Purwandari (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research aims to examine the influence of parental roles in the era 4.0 on students' academic achievement at MI Islamiyah Pinggirsari Tulungagung using a quantitative approach. The research population includes all students at MI Islamiyah Pinggirsari Tulungagung, with a sample size of 32 students from Class IX B. The main instrument is a questionnaire designed to collect data on the influence of parents and students' academic achievements. Statistical analysis uses a simple linear regression analysis. The validity test results show that the variables of parental influence in the era 4.0 and students' academic achievements have a significant correlation, indicating the instrument's validity. The reliability test produces an accepted value of Cronbach's Alpha, indicating a good level of instrument reliability. Simple regression analysis produces a determination coefficient of 50.4%, indicating that the parental influence variable in the era 4.0 contributes to that extent to the variation in students' academic achievements. The ANOVA test indicates the significance of the regression model, and the positive regression coefficient indicates that parental influence in the era 4.0 has a positive impact on students' academic achievements. Descriptive hypothesis testing shows that students' perceptions of parental influence in the era 4.0 and students' academic achievements are generally at a good level, with percentages of 95.9% and 98.4%, respectively, according to the specified classification. This study is expected to provide a deeper understanding of how parental roles in the era 4.0 affect students' academic achievements at MI Islamiyah Pinggirsari Tulungagung and has the potential to contribute to the development of education strategies that align with the demands of the times.